Influence of Osmotic Solution and Vacuum Condition on the Quality of Iron-Supplemented Asian Seabass (Lates calcarifer) Fillet by Osmosis - Thaiwong, Numphon; Klapthaplang, Salinee; Kachenpukdee, Natta (YRU Journal of Science and Technology, 2022)
The objective of this research was to optimize the suitable osmotic solution and condition for the iron-supplemented barramundi fillet production by osmosis. Ferrous sulfate was applied as an iron supplement at the concentration about 0.2, 0.4, 0.6, 0.8 and 1% in the osmotic solution. The result found that barramundi fillet after osmosis from the use of 10% sodium chloride and 40% glucose as the osmotic solution in vacuum soaking was the highest values of water loss (8.82 ± 0.15%) and solid gain (6.84 ± 0.16%) at 240 min. The iron content of barramundi fillet (control) indicated about 0.37 mg/ 100 g samples. The increasing of ferrous sulphate concentration in osmotic solution affected a greater iron content of samples in the range of 12.4 – 62.0 mg/100 g sample. The iron supplantation of barramundi fillet altered the color value as the decreasing of L* a* and b* values. However, the sensory evaluation result of iron-supplemented barramundi fillet which osmosis in 1% ferrous sulfate was as like moderately in overall attribute.